CD24 interacts with and promotes the activity of c-src within lipid rafts in breast cancer cells, thereby increasing integrin-dependent adhesion - Baumann, Petra; Thiele, Wilko; Cremers, Natascha; Muppala, Santoshi; Buchert, Justyna; Mudduluru, Giridhar; Allgayer, Heike; Sleeman, Jonathan P. (Cellular and molecular life sciences, 2012)
Expression of the glycosylphosphatidylinositol-anchored membrane protein CD24 correlates with a poor prognosis for many human cancers, and in experimental tumors can promote metastasis. However, the mechanism by which CD24 contributes to tumor progression remains unclear. Here we report that in MTLy breast cancer cells CD24 interacts with and augments the kinase activity of c-src, a protein strongly implicated in promoting invasion and metastasis. This occurs within and is dependent upon intact lipid rafts. CD24-augmented c-src kinase activity increased formation of focal adhesion complexes, accelerated phosphorylation of FAK and paxillin and consequently enhanced integrin-mediated adhesion. Loss and gain of function approaches showed that c-src activity is necessary and sufficient to mediate the effects of CD24 on integrin-dependent adhesion and cell spreading, as well as on invasion. Together these results indicate that c-src is a CD24-activated mediator that promotes integrin-mediated adhesion and invasion, and suggest a mechanism by which CD24 might contribute to tumor progression through stimulating the activity of c-src or another member of the Src family.